Effect of Interleaving Exemplars Presented as Auditory Text on Long- term Retention in Inductive Learning - Norehan, Zulkiply (Elsevier Ltd., 2013)
The present study investigated the exemplar interleaving effect on long-term retention in the context of inductive learning. In particular, an experiment using aurally presented texts was conducted to examine whether or not the benefits of interleaving of exemplars from several categories vary with retention interval in inductive learning. Participants studied a series of aurally presented texts from several categories which were presented massed and interleaved, and later their induction was tested either shortly after the study phase (short-term retention) or after a week‘s delay (long-term retention). Consistent with findings from previous studies, the interleaving effect was found in the short-term retention condition, and crucially, the present study extended the generalisability of the interleaving effect in the long-term retention condition to aurally presented texts. Interestingly, participants judged massing to be more effective than spacing (interleaving) though their actual performance showed the opposite. The present study provides further evidence that interleaved exemplars have considerable potential in improving inductive learning in the long term.